Redesigning the Production Facility Layout Using the Systematic Layout Planning (SLP) Method: A Case Study at CV. Vyo Factory - Rahmadani, M. Ibnu; Nur Diansari, Brillian; Filemon Waluyono, Garnet (SAINTEKBU, 2025)
This research was conducted to design a facility layout using the SLP method, accompanied by a comparison of the efficient time between the initial layout and the proposal, as well as the results of direct observations of the production flow and activities in the CV production area. The Vyo factory has problems with irregular production flows, back-and-forth material movement (backtracking). This problem can have an impact on the enormous distances that material is moved irregularly due to relationships between departments that are far apart. Additionally, there is the issue of placing facilities that are not connected, as some facilities must be located near the production process. To overcome layout management problems, a method that can be employed is Systematic Layout Planning, which can be implemented using SketchUp software by redesigning the facility layout using this method. Based on the proposed alternative layout design using the SLP method, it can be seen that the best layout for shirt production on line 1 is starting with the storage warehouse, leading to the cutting for pattern cutting, after completion, it continues with a sewing process combining the front and back chest patterns, and sleeve sewing. The results of the design carried out using the SLP method, with SketchUp software, obtained a proposed layout to eliminate backtracking. The results of the analysis of effectiveness and efficiency during the production process can optimize the production process to be more orderly and utilize space more efficiently, allowing for a more streamlined workflow from incoming raw materials to finished products. Implementing this proposed layout can resolve layout issues in the production area, thereby eliminating backtracking.